À l’ombre des grandes puissances de Mésopotamie. Une histoire du Sūhu à l’époque néo-assyrienne - Clancier, Philippe, author.
1 online resource.
Keywords: In À l’ombre des grandes puissances de Mésopotamie. Une histoire du Sūhu à l’époque néo-assyrienne , Philippe Clancier studies the Sūhu region of the Euphrates river, on the border of Assyria and Babylonia. He reconstructs its geography by presenting the fauna and flora, and by identifying sites and the layout of traffic routes. After going back to the 2nd millennium BC to explain the origin of its main dynasty, he highlights the partition of Sūhu into two main kingdoms before its reunification in the 8th century BC and its later conquest by Assyria. Thanks to an interdisciplinary approach that combines written sources, archaeological data and travellers’ accounts, Philippe Clancier offers for the first time a history of this region in the neo-Assyrian period.